2022
DOI: 10.1038/s41598-022-13193-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring hot spots of short birth intervals and associated factors using a nationally representative survey in Bangladesh

Abstract: Short Birth Interval (SBI, defined as < 33 months interval between the two most recent births or < 24 months between one live birth to the next pregnancy) is a public health problem in most low- and lower-middle-income countries. Understanding geographic variations in SBI, particularly SBI hot spots and associated factors, may help intervene with tailored programs. This study identified the geographical hot spots of SBI in Bangladesh and the factors associated with them. We analyzed women’s data extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 48 publications
1
18
1
Order By: Relevance
“…Improving the uptake of maternal and postnatal healthcare services are also key to the prevention of neonatal and infant mortality. Access to family planning services and use of contraception, including access to contraception at the post-partum period, should also be ensured, particularly among the disadvantaged and unaware population where occurrence of birth in short interval is very higher 16,42 . Existing health problems, including maternal undernutrition and anaemia, are required to be addressed properly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the uptake of maternal and postnatal healthcare services are also key to the prevention of neonatal and infant mortality. Access to family planning services and use of contraception, including access to contraception at the post-partum period, should also be ensured, particularly among the disadvantaged and unaware population where occurrence of birth in short interval is very higher 16,42 . Existing health problems, including maternal undernutrition and anaemia, are required to be addressed properly.…”
Section: Discussionmentioning
confidence: 99%
“…<18 years) or later (>34 years) in the reproductive life course, pregnancies of a shorter interval (<24 months) and higher parity (i.e., more than two children) are common in LMICs 14 . In Bangladesh, the prevalence of early pregnancy (43%), short pregnancy interval (26%), higher parity (24%) are very high in Bangladesh and a significant proportion of pregnancies occur among women with more than one of these specific high risk behaviours [15][16][17] . These independent higher-risk fertility behaviour components have been found to interact with each other and adversely affect several maternal health outcomes, including chronic undernutrition and pregnancy complications, which is a risk factor for increased obstetric and newborn complications 14,[18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…This linkage may arise in direct and indirect ways: (i) women having these characteristics, such as early marriage, prefer births in short intervals, and (ii) short interval births increase adverse outcomes, such as pregnancy complications and maternal and under-five nutrition. The associations are mediated by other factors, including the disadvantaged socioeconomic conditions of the mothers, previous child survival status, and the distance from home to nearby clinics [12][13][14]. These linkages indicate a potential association between SBI and under-five mortality.…”
Section: Introductionmentioning
confidence: 91%
“…Consequently, respondents' options to get healthcare knowledge and contraception accessibility, which is an important determinant of short birth intervals, have been narrowed over the years [9]. This influences the socio-demographic disadvantaged women mostly, among which births in short interval are highly prevalent [14,15,16,68].…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies in different settings have reported a varying level of suboptimal birth spacing practice among reproductive-age women. Studies based on single-country data revealed that 23%, 26%, 47%, 49%, and 50% of reproductive-age women in Pakistan [ 12 ], Bangladesh [ 13 ], Ethiopia [ 14 ], Ghana [ 15 ], and rural India [ 16 ] respectively had experienced shorter birth interval. Furthermore, a secondary analysis of demographic and health survey (DHS) data showed that the prevalence of suboptimal birth spacing was 59% in ten high-fertility African countries [ 17 ] and 56% in thirteen Sub-Saharan African (SSA) countries [ 18 ].…”
Section: Introductionmentioning
confidence: 99%